Optimizing Multimodal Gender Literacy Skills with Innovative Approaches through Digital Learning Transformation - Arozatulo Bawamenewi; Riana Riana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to optimize multimodal gender literacy skills through an innovative approach in digital learning transformation. This research was conducted in high schools involving students from various gender backgrounds. The research method used is a qualitative method with a descriptive approach. Data were collected through multimodal literacy skills tests, classroom observations, and interviews with students and teachers. The results of the study show that innovative approaches in digital learning transformation significantly improve students' multimodal literacy skills. In addition, this approach also helps reduce the gender gap in multimodal literacy, by providing equal opportunities for male and female students to thrive. From the results of the study obtained from women's data, 65% of female respondents showed a high preference for activities involving text and images, while 70% of male respondents preferred activities involving audio and video. Based on the results of the research, it was concluded that using an innovative approach can optimize multimodal gender literacy skills.